Customer knowledge management, trust, commitment and customer lifetime value in islamic insurance industry - Abu Hassan, Lailatul Faizah; Wan Jusoh, Wan Jamaliah; Hamid, Zarinah (2012)
This study is to examine the influence of customer knowledge management on customer lifetime value in the Islamic insurance industry. A research framework is proposed to determine the relations between customer knowledge management, trust, commitment and customer lifetime value. The population of the study will consist of customers who have subscribed to the Islamic insurance products and services. Four main regions in Malaysia namely North, South, East and Central will be selected as a study setting for this study. Structural Equation Modeling will be applied to test the constructs’ relationships. It is expected that findings from this study will contribute to the existing literature to both theoretical and managerial approaches in order to better understand the pattern of customer knowledge management and customer lifetime value, especially in Islamic insurance industry settings.